Locke and the formation of the gentleman - Christian Lindberg Lopes do Nascimento (IXTLI, 2014)
This paper’s main objective is to analyze the concept of training within John Locke’s educational work. Yet this discussion is entered in the moral perspective supported by this English philosopher. Although, it is possible to realize that the intended training has in gentleman your central target. Besides the philosopher’s educational texts, this debate involves his other theoretical contributions, especially the relationship between education and political theory. Thus, it was not excused the adoption of Locke’s other manuscripts and commentators that were relevant to the argumentation. Finally, we adopted as methodological procedures: reading, analysis and interpretation of selected texts.